A statistical analysis project study on Vinyl Resources, Inc. - Dunuan, Lara Mia (College of Engineering, 2002)
Vinyl Resources, Inc, is a 100 percent Filipino corporation engaged in the manufacture of refrigerator and freezer door gaskets and other polyvinyl extruded products. It was incorporated in 1988 and at present is now a fully integrated manufacturer with a capacity of 300 tons per annum, supplying major appliance manufacturers and bottle cooler makers. Gasket rejects due to their final cut length achieved at the magnet-insertion stage were observed for the months of July, August, September and November for the year 2001. A problem identified in the magnet-insertion stage is the observed variance in the final cut length achieved. A certain gasket model has a specified cut length. Any achieved cut length which is lower or higher than the specified length is rejected. The gasket model having the highest rejection rate for that period is 10 SD SR (Size 10 Side Door of Side Refrigerator), contributing 26.70 percent of rejection.The Goodness of Fit Test is used to verify if the data points follow a normal distribution. Two-Factor Analysis is performed to determine the presence or absence of the effect of the two factors and their interaction. The two factors considered were the machine cutting length setting used and the time of production during the day. The Duncan's Multiple Range Test and the Graphical Comparison of Means and Variances are used to compare the means and variances produced by the two factors and their interaction. These tests also determine which treatment level gives the best result for the final cut length of the gaskets. From the tests performed, the following results were obtained : (1) only the interaction between time and machine cutting length setting has a significant effect on the final cut length achieved; (2) the treatment level results are significantly different from each other; and (3) the interaction of time range 2 (11 AM-5 PM) with the machine cutting length setting range 2 (1623 mm-1628 mm) yields the best cutting length results.